Pemilihan Supplier Baja Dies GDC di PT. XYZ Menggunakan Metode Analytical Hierarchy Process (AHP) - Hamdani Aris; Puput Rahmawati; Joko Prasetiyo; Reynald Fatah Atlantika4 (JERA : Journal of Engineering Research and Application, 2023)
The conflict between Russia and Ukraine has impacted the global market, resulting in monthly increases in steel and iron ore prices. PT. XYZ is an automotive company, and one of its products is GDC (Gravity Die Casting) dies, which are manufactured using steel raw material sourced from various alternative suppliers. This study employs the Analytical Hierarchy Process (AHP) method to select the optimal steel supplier. The analysis reveals that, in the process of selecting steel suppliers at PT. XYZ, the price factor carries the highest priority weight, followed by quality criteria as the second priority, the delivery factor as the third priority, and the service factor as the fourth priority criterion. Based on the analysis of criteria and subcriteria in the supplier selection process, Supplier B is evaluated as the top choice with the highest priority, followed by supplier A as the second priority, and Supplier C as the final option. This research provides valuable insights for PT. XYZ in making decisions related to steel supplier selection. By considering aspects such as price, quality, delivery, and service, the company can optimize the supplier selection process in alignment with its needs and business strategy. Keywords: Analytical Hierarchy Process (AHP), supplier selection, supplier